Marketing Strategies for Sweet Potato Chips: a Case Study of CV. Mitra Mandiri, Mojokerto - Sudarno; Dewi, Yuni Rosita; Anam, Khoirul (Politeknik Negeri Jember, 2024)
After the Covid-19 pandemic, the marketing of sweet potato chips produced by CV Mitra Mandiri has become limited. The purpose of this research is to analyze the internal and external factors in the marketing of sweet potato chips, to develop alternative marketing strategies for sweet potato chips, and to determine the appropriate marketing strategy for sweet potato chips. This research utilizes the IE Matrix (Internal-External), SWOT Matrix (Strengths, Weaknesses, Opportunities, Threats), and QSPM (Quantitative Strategic Planning Matrix) analysis. The results of the IE Matrix analysis indicate that CV. Mitra Mandiri in cell V can implement strategies to survive and sustain itself. Based on alternative strategies, the priority strategy with the highest value of 7.57 is to enhance human resources for market control of sweet potato chips through digital marketing.